EFL Academic Writing Challenges under Divided Responsibility: An Academic Literacies Analysis Informed by Lea and Street - Ummu Rofikah (Pendiri: Jurnal Riset Pendidikan, 2026)
Academic writing challenges in EFL higher education are often framed as deficiencies in students’ language and writing skills, with less attention to the pedagogical and institutional conditions through which academic writing is taught. This study investigated challenges perceived by current students, course-experienced students, and lecturers in a Writing for Academic Purposes course at an Indonesian university. A quantitatively driven explanatory sequential mixed-methods design was employed. Questionnaire data from 153 participants were summarized using item-level mean scores, while semi-structured interviews with 12 participants were analyzed through Reflexive Thematic Analysis. Lea and Street’s Academic Literacies Model served as a sensitizing theoretical lens. The quantitative findings indicated recurring concerns related to AI literacy instruction, feedback, interpersonal interaction, teaching variation, instructional constraints, and difficulties across ideation, planning, drafting, and revision. The qualitative analysis developed four themes: standards without dialogue, scaffolding without agency, AI as unofficial writing infrastructure, and writing development under divided responsibility. In this study, divided responsibility refers to the distribution of responsibility for writing development across student engagement, pedagogical practices, and institutional conditions rather than its attribution to learners alone. Taken together, the findings suggest tensions among technical skills instruction, academic socialization, student agency, institutional expectations, and emerging AI-mediated writing practices. The study highlights the need for more dialogic feedback, transparent assessment, agency-oriented scaffolding, and explicit critical AI literacy in EFL academic writing instruction.